1991
DOI: 10.1073/pnas.88.22.9954
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the staphylococcal enterotoxin A superantigen binding site in the beta 1 domain of the human histocompatibility antigen HLA-DR.

Abstract: The staphylococcal enterotoxin A (SEA) is a superantigen that must bind to class II molecules of the major histocompatibility complex to be recognized by T cells. In humans, most HLA-DR class II allelic and isotypic forms, such as DR1, bind SEA well. DRw53 is an exception, binding SEA very poorly. We have localized this difference to a single residue (amino acid 81) in the fl1 domain. A highly conserved histidine at residue 81 allows SEA binding, but a tyrosine does not. Residue 81 is predicted to lie in an a-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
67
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 40 publications
7
67
0
Order By: Relevance
“…It is unlikely that costimulation influences allo-antigen and superantigen reactivity, but reports have demonstrated that a cell's peptide repertoire can influence allogeneic T-cell responses and superantigen binding. 63,64 Invariant chain and DM activity determine the peptide repertoire and, in turn, the cell's ability to present superantigen and elicit allogeneic responses. 65 Therefore, it remains possible that CVEs have altered invariant chain and DM activity that influence their peptide repertoire, affecting their ability to elicit alloreactivity and to bind superantigen.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that costimulation influences allo-antigen and superantigen reactivity, but reports have demonstrated that a cell's peptide repertoire can influence allogeneic T-cell responses and superantigen binding. 63,64 Invariant chain and DM activity determine the peptide repertoire and, in turn, the cell's ability to present superantigen and elicit allogeneic responses. 65 Therefore, it remains possible that CVEs have altered invariant chain and DM activity that influence their peptide repertoire, affecting their ability to elicit alloreactivity and to bind superantigen.…”
Section: Discussionmentioning
confidence: 99%
“…Each member has its unique biochemical and serological properties, but shares significant homology in sequence, structure, and biological functions with other family members (1,6). Staphylococcal enterotoxins are also characterized as "superantigens" with all members activating large numbers of T cells bearing particular TCR V~ elements (7)(8)(9). As a result of T cell activa-1 Abbreviations used in this paper: FPLC, fast protein liquid chromatography; LB, Luria-Bertani medium; pI, isoelectric point; SEA, SEB, SEC1, SEE, staphylococcal enterotoxins A, B, C1, D, and E, respectively; TSS, toxic shock syndrome; TSST-1, TSS toxin 1. tion, T cell proliferation and cytokine expression are profoundly elevated.…”
mentioning
confidence: 99%
“…The binding sites for several staphylococcal toxins have been identified. The structurally similar toxins staphylococcal enterotoxins A and E (SEA and SEE) bind to a conserved region of the class II ( chain including the histidine residue at position 81 (17,18). Toxic shock syndrome toxin (TSST) requires sequences in the al domain for high-affinity binding to human class II (19) and in both the al and (31 domains of mouse class II (20).…”
mentioning
confidence: 99%